DOI: 10.14264/uql.2019.162
|View full text |Cite
|
Sign up to set email alerts
|

The role of sloughing on the pathophysiology of chytridiomycosis in amphibians

Abstract: Amphibians periodically remove the dead skin layer through a process known as sloughing.Because of their thin semi-permeable skin, sloughing is important to maintain skin integrity and biological functions such as ionic and osmotic regulation. However, sloughing has been shown to affect cutaneous ion and water movements, temporarily disrupting osmotic homeostasis. Since sloughing occurs regularly in amphibians, every 1-14 days depending on the species and temperature, it is important to assess the potential ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 309 publications
(698 reference statements)
0
4
0
Order By: Relevance
“…Sloughing has been shown to significantly increase the permeability of the skin, leading to increased ion efflux (79), increased water uptake rates when in water (22,34), and increased rates of water loss in dry environments (62). Although the ionic and osmotic disruption to the skin during sloughing can be substantial, we have shown that in healthy amphibians there is no evidence of a loss of internal ion homeostasis (77,79). We hypothesize that sloughing frogs may upregulate the transcellular and/or paracellular movement of water to compensate for the increase in skin permeability after sloughing.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Sloughing has been shown to significantly increase the permeability of the skin, leading to increased ion efflux (79), increased water uptake rates when in water (22,34), and increased rates of water loss in dry environments (62). Although the ionic and osmotic disruption to the skin during sloughing can be substantial, we have shown that in healthy amphibians there is no evidence of a loss of internal ion homeostasis (77,79). We hypothesize that sloughing frogs may upregulate the transcellular and/or paracellular movement of water to compensate for the increase in skin permeability after sloughing.…”
Section: Introductionmentioning
confidence: 73%
“…However, increased sloughing frequency can be detrimental for some frog species that are unable to remove the fungus completely or quickly enough (50). In these frogs, the combined effect of increased sloughing frequency and damage from Bd further exacerbates the loss of cutaneous functions (77,78).…”
Section: Introductionmentioning
confidence: 99%
“…A naïve Boolean search string [(Batrachochytrium OR chytrid*) AND (frog OR toad OR amphibia* OR anur* OR Caudat* OR Urodela OR salamand*)] was first performed on Web of Science on the October 28, 2021, resulting in 2113 records. The full record from the naïve search and citations in Table S1.1 from Wu (2019) were exported to R 4.1.0 (R Core Team, 2021) for keyword co‐occurrence network analysis (Supplementary Figure S1) using the litsearchr package (Grames et al, 2019). This was used to create a comprehensive Boolean search string for both Web of Science and Scopus detailed in the Supplementary Figure S2.…”
Section: Methodsmentioning
confidence: 99%
“…I focused on post-metamorph amphibians as Bd infection in tadpoles does not cause mortality directly (Rachowicz & Vredenburg, 2004). S1.1 from Wu (2019) were exported to R 4.1.0 (R Core Team, 2021) for keyword co-occurrence network analysis (Supplementary Figure S1) using the litsearchr package (Grames et al, 2019). This was used to create a comprehensive Boolean search string for both Web of Science and Scopus detailed in the Supplementary Figure S2.…”
Section: Introductionmentioning
confidence: 99%